Determinant of Unmet Need for Family Planning in East Java Province Analysis of 2015 Inter-Census Population Survey Data - Lutfi Agus Salim (Indian Journal of Forensic Medicine & Toxicology, 2020)
One of the government’s efforts to control population growth is Family Planning program and one indicator of its performance is unmet need for contraception. Based on 2015 Inter-Census Population Survey Data, East Java is one of the provinces with high unmetneed events in Indonesia. Unmet need for contraceptive in East Java is 16.3 percent. This study examines factors that correlate with unmetneed in East Java. Chi-square test used to find correlation between independent variables and unmetneed. The data used is the 2015 Inter Census Population Survey Data - East Java Province. The results showed age, area of residence, work status, education, and number of children are related to unmetneed events. Interventions that should be undertaken are improving counseling, communication, information and education, fulfilling demand of contraception and making it easier to access family planning.